Morphometric evaluation of C1 pedicle and lateral mass for screw fixation in Kelantan : feasibility study using CT scan - Meng, Teo Yu (2017)
Introduction Posterior arch or pedicle screw is an alternative fixation method to lateral mass screw of the altas (C1). Several studies had shown its advantages over conventional C1 lateral mass screw. The most important factor to determine the feasibility of posterior arch screw insertion is the vertical pedicle height of posterior arch, which several studied had proved its feasibility . However, it must be used with caution in our population as the posterior arch size may not be able to accommodate the conventional 3.5mm pedicle screw. Hence, we performed a mophormetric study of C1 vertebrae using CT scan to determine the feasibility of screw insertion. Materials and methods We performed a cross sectional study to analyse 113 C1 veterbrae using CT using 1.0mm slice thickness. Those who had fracture of C1, infection of C1, tumorous condition of C1 and any congenital deformities of C1 were excluded from this study. Desired axial and sagittal CT scan slices was obtained for measurement after reconstruction of images and slice through the desired anatomical landmark. Each parameter was defined anatomically using appropriate landmark. All the parameters were measured up to 0.1mm twice and the mean was taken, and the statistical analysis was done using SPSS version 20. Independent t-test was use to determine the significant difference between sides and gender. Descriptive analysis for numerical variables were described as mean.Results The mean outer pedicle height were 3.5 mm for right and left sides. All lateral mass height in 82 male patients were more than 3.5mm. 19.5%(right) and 25.6%(left ) of lateral mass height in male patients are smaller than 4.0mm. For outer pedicle height in 82 male patients, 43.9%(right) and 40.2%(left) were smaller than 3.5mm,79.3%(right) and 78%(left) were smaller than 4.0mm. For lateral mass height in 31 female patients, 12.9%(right) and 9.7%(left ) were smaller than 3.5mm, 48.4%(right) and 51.6%(left ) were smaller than 4.0mm, 83.9%(right) and 90.3%(left) were smaller than 4.5mm. For outer pedicle height in female patients, 77.6%(right) and 74.2